Arginylation Regulates G-protein Signaling in the Retina - Fina, Marie E.; Wang, Junling; Vedula, Pavan; Tang, Hsin-Yao; Kashina, Anna; Dong, Dawei W. (Frontiers in Cell and Developmental Biology, 2022)
Arginylation is a post-translational modification mediated by the arginyltransferase (Ate1). We recently showed that conditional deletion of Ate1 in the nervous system leads to increased light-evoked response sensitivities of ON-bipolar cells in the retina, indicating that arginylation regulates the G-protein signaling complexes of those neurons and/or photoreceptors. However, none of the key players in the signaling pathway were previously shown to be arginylated. Here we show that Gαt1, Gβ1, RGS6, and RGS7 are arginylated in the retina and RGS6 and RGS7 protein levels are elevated in Ate1 knockout, suggesting that arginylation plays a direct role in regulating their protein level and the G-protein-mediated responses in the retina.